Slipping through the cracks: teachers who miss out on early career support. Issue 3 (27th May 2018) - Kelly, Nick; Sim, Cheryl; Ireland, Michael
ABSTRACT: This paper presents evidence from a nationally representative sample of early career teachers about those likely to miss out on formal support, and the employment conditions associated with this absence of support. It uses survey data from the Staff in Australia's Schools Survey. Consistent with existing research, our results suggest a relationship between early career teachers with insecure employment and a lack of support. The findings suggest that, for early career teachers, being unsupported is associated with dissatisfaction with professional relationships and career opportunities; and that this dissatisfaction is associated with an intention to leave the profession.